Phenotypic variation in male Calopteryx splendens damselflies: the role of wing pigmentation and body size in thermoregulation - Laakso Linda K.; Ilvonen Jaakko J.; Suhonen Jukka (OXFORD UNIV PRESS, 2022)
For ectothermic insects, their colour and size are important determinants of body temperature: larger bodies require more heat to reach a certain temperature, and dark colours absorb heat more efficiently. These dark colours are expressed using melanin, which has been intimately linked with the thermoregulatory capabilities of insects. Melanin is also linked with immune defence and is often used as a secondary sexual character in insects. There is a potential trade-off situation between thermoregulatory capabilities, immune defence and secondary sexual characters, all of which use melanin. Some Calopteryx damselflies, such as Calopteryx splendens, have melanin-based wing pigmentation that is sexually selected and drives intra- and interspecific territorial aggression. Our goal was to study experimentally how the wing pigmentation and body size of C. splendens males affect their thermoregulation and, especially, their ability to become active (hereafter, 'activate') after being cooled down. Our results were in line with our hypotheses, showing that individuals with larger wing spots had significantly faster activation times than those with smaller wing spots, and that individuals with larger body size had significantly slower activation times than those with smaller body size. Both variables showed an interaction and are therefore important in damselfly warm-up and activation. We discuss the role of wing pigmentation and thermoregulation in the behavioural patterns observed in Calopteryx species.